The Continuing Relevance of Common Law Property Rights and Remedies in Addressing Environmental Challenges - Grinlinton, David (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2017)
Environmental protection and natural resources management is today dominated by legislative measures and administrative procedures. Enforcement and penalty regimes for environmental damage and the management of natural resources are all highly regulated. Nevertheless, there remains the oft-neglected realm of common law rules and procedures available to individuals and public interest groups, and indeed government, as alternate or supplementary mechanisms to enforce rights and obligations, to guide the implementation and interpretation of environmental regulation, and to provide new avenues for addressing environmental challenges.The common law, particularly in the areas of tort and property, has demonstrated remarkable adaptability in addressing novel environmental threats and in innovating to protect environmental values and incentivize ecologically-sustainable development of natural resources. This article is intended to provide a review of the historical and current contribution of the common law, focusing particularly on property law concepts and property-related torts, and to explore the future potential of those mechanisms in contributing to environmental protection and environmentally-sustainable development. The article draws on cases and developments in a number of similar common law jurisdictions, including Canada, the United Kingdom, the United States, Australia, and New Zealand.